Entrepreneurial Orientation and Entrepreneurial Marketing Behaviours among Nigerian Entrepreneurs - J.C. , Anetoh; E.C. , Ndubisi; Anetoh , Vivian (African Journal of Education,Science and Technology (AJEST), 2017)
This work examined the relationship between entrepreneurial orientation and entrepreneurial marketing behaviours among Nigerian Entrepreneurs using Anambra State as reference point. Entrepreneurial orientation and entrepreneurial marketing behaviours are very important concepts needed by entrepreneurial enterprises in order to survive the competitive challenges of time and also run their enterprises well. The study utilized 118 usable copies of questionnaire and evaluated the relationship between entrepreneurial orientation and entrepreneurial marketing behaviours among Nigerian Entrepreneurs with reference to Anambra area. Pearson Product Moment Coefficient of Correlation was used to test the five formulated hypotheses necessitated using SPSS software package. The results indicated that there is significant relationship between entrepreneurial innovativeness, proactiveness, risk-taking, autonomy, competitive aggressiveness and entrepreneurial marketing behaviours among Nigerian Entrepreneurs. The major findings revealed that all entrepreneurial orientation dimensions are significantly correlated to entrepreneurial marketing behaviour among Nigerian Entrepreneurs. The conclusion drawn from the study is that significant relationship exist between entrepreneurial orientation and entrepreneurial marketing behaviours among Nigerian Entrepreneurs. The study recommends that Nigerian Entrepreneurs should continue to advance on their entrepreneurial orientation dimensions for enhanced entrepreneurial marketing behaviors among Nigerian Entrepreneurs as well as been consistent in maintaining high level of competitiveness in order to remain in business.